2015
DOI: 10.1177/2211068215573924
|View full text |Cite
|
Sign up to set email alerts
|

Toward Microbioreactor Arrays: A Slow-Responding Oxygen Sensor for Monitoring of Microbial Cultures in Standard 96-Well Plates

Abstract: In this study, a slow-responding chemo-optical sensor for dissolved oxygen (DO) integrated into a 96-well plate was developed. The slow response time ensures that the measured oxygen value does not change much during plate transport to the microplate reader. The sensor therefore permits at-line DO measurement of microbial cultures. Moreover, it eliminates the necessity of individual optical measurement systems for each culture plate, as many plates can be measured successively. Combined with the 96-well format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that the technology can be easily combined with conventional approaches to yield not only higher amount of a target protein through the higher cell density [ 21 , 25 , 26 ], but also in many cases a higher amount of correctly folded protein per cell [ 26 , 27 ]. Modern screening systems, such as RAMOS, Biolector and PreSens’ SensorDish with an ability for on-line monitoring of growth data provide excellent tools to optimize the growth and expression conditions [ 28 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the technology can be easily combined with conventional approaches to yield not only higher amount of a target protein through the higher cell density [ 21 , 25 , 26 ], but also in many cases a higher amount of correctly folded protein per cell [ 26 , 27 ]. Modern screening systems, such as RAMOS, Biolector and PreSens’ SensorDish with an ability for on-line monitoring of growth data provide excellent tools to optimize the growth and expression conditions [ 28 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the newly developed growth systems, such as EnPresso, are widely compatible with a number of cultivation vessels from high-throughput small scale, over shake-flasks to larger reactors [ 48 , 92 95 ], even in robotic automated set-ups [ 32 , 96 ]. The scalability of such a system has been demonstrated for the production of different proteins by Glazyrina et al [ 97 ], Li et al [ 75 ] and Šiurkus et al [ 22 , 48 , 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxygen-sensing fluorophores have been embedded in hydrogel inserts to monitor dissolved oxygen levels in custom 96-well plates up to several hours ( Wu et al, 2018 ). Another bacterial cell culture study monitored peri-cellular oxygen by methods similar to the ones reported here, including the use of a commercial 96-well OxoPlate by Presens ( Glauche et al, 2015 ). In one variant, circular sensor patches were cut and glued in standard 96-well plates; a robotic arm was moving the plate between a shaker and a plate reader to track oxygen levels as function of shaking speeds to optimize microbial culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[21] In addition, this system was successfully applied for parallel continuous cultivations [23,24] and a first prototype of an add-on system consisting of micropumps was reported for feeding and pH correction using small volumes at high frequency. [25] However, the application of non-invasive optical biomass measurements based on turbidity or light scattering is difficult in these MBR systems, since the continuously agitated impellers and resulting submerse gas bubbles interfere with [127][128][129][130] www.advancedsciencenews.com www.biotechnology-journal.com such optical measurements. Therefore, the two systems currently rely on manual sampling for biomass determination, and here robotic integration seems to be mandatory to avoid shifting the bottleneck from cultivation to analysis.…”
Section: Mbr Systems Based On Stirred Cultivation Unitsmentioning
confidence: 99%